2016
DOI: 10.1016/j.jclepro.2015.10.133
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the preferences and pro-environmental behavior of college students: the effects of years on campus, demographics, and external factors

Abstract: Models from several social science fields have identified factors that lead to proenvironmental behavior. This research builds on those models by analyzing a survey completed by over 500 undergraduates at a US liberal arts university to examine the characteristics of students that are associated with more environmentally friendly behavior and quantify the desirability of different environmental initiatives. There is evidence that the probability of pro-environmental behavior substantially increases with each a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
75
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 44 publications
11
75
0
2
Order By: Relevance
“…Academic factors also predicted behavioral intention (explaining 7.8% of explained variance) and sustainable lifestyle (explaining 5.7% of explained variance). This is consistent with findings by Meyer [2] that pro-environmental behavior increases with additional time spent in higher education environments.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Academic factors also predicted behavioral intention (explaining 7.8% of explained variance) and sustainable lifestyle (explaining 5.7% of explained variance). This is consistent with findings by Meyer [2] that pro-environmental behavior increases with additional time spent in higher education environments.…”
Section: Discussionsupporting
confidence: 93%
“…Informal learning that occurs in formal higher learning environments may be an essential source of sustainable behavior [2]. In our model, perceived teaching methods for learning SD were examined as a possible predictor.…”
Section: The Role Of Teaching Methods Supporting Authentic Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender and education level were often found as significant predictors of PEBs. Meyer (2016), for instance, demonstrated that individuals obtaining a higher education degree reported a higher level of engagement in PEBs. Sanchez et al (2016) demonstrated that females reported a significantly higher level of involvement in green purchasing behavior than did males.…”
Section: Theoretical Contextmentioning
confidence: 99%
“…In social science, the endeavors of sociologists and psychologists may be divided into two basic lines of research [4]. One of these research lines has focused on identifying the sociodemographic factors related to pro-environmental behavior, such as gender [5], age [6], place of residence [7], ethnicity [8], income [9] and education [10]. Another line has focused on the influences of social-psychological determinants, such as the influence of values, norms, attitudes, sense of control, personality and place attachment on pro-environmental behavior and has been tested over the last 40 years [11].…”
Section: Introductionmentioning
confidence: 99%